2015
DOI: 10.1088/0256-307x/32/7/074206
|View full text |Cite
|
Sign up to set email alerts
|

Single Mode 2 μm GaSb Based Laterally Coupled Distributed Feedback Quantum-Well Laser Diodes with Metal Grating

Abstract: Room-temperature operation of a GaSb based laterally coupled distributed feedback quantum-well laser diode emitting at 2 𝜇m is demonstrated. The device exhibits single longitudinal mode characteristic as a result of the first order Cr-Bragg gratings alongside the narrow ridge waveguide. We design the laser structure to obtain a critical coupling condition corresponding to a coupling coefficient of 12 cm −1 . For a 1-mm-long uncoated laser diode with a 3-𝜇m-wide stripe, a single mode output spectrum with side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Molecular gases often show significantly stronger absorption within the mid-infrared (MIR) than in the near-infrared or visible spectral regime. In this MIR region, many important gases have significant absorption lines that are crucial in healthcare, production supervision, and safety and environmental monitoring [1][2][3]. For this work, we restricted ourselves to methane, which is a major greenhouse gas and a monitor gas for lung cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular gases often show significantly stronger absorption within the mid-infrared (MIR) than in the near-infrared or visible spectral regime. In this MIR region, many important gases have significant absorption lines that are crucial in healthcare, production supervision, and safety and environmental monitoring [1][2][3]. For this work, we restricted ourselves to methane, which is a major greenhouse gas and a monitor gas for lung cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Among the diverse schemes, incorporating an appropriate light management structure is an effective way of improving light absorption without increasing the thickness of the photoactive layers, and thus has been developed into one of the frontiers. It has been suggested that various antireflection structures, [13][14][15][16][17][18] photonic crystals, [19][20][21][22][23][24] metallic nanoparticles, [25][26][27][28][29][30] and gratings [31][32][33][34][35][36] be used to enhance light absorption of the relevant devices. However, it is notable that the balance between light absorption enhancement and complexity of the light management structures should be seriously taken into consideration for solar cell applications.…”
Section: Introductionmentioning
confidence: 99%
“…Tunable diode laser absorption spectroscopy (TDLAS) is a versatile and robust method for gas sensing with applications ranging in industry, health and safety (e.g., toxic gas, alcohol, and explosives), and medicine [1][2][3]. Gallium antimonide (GaSb) is an important material system for single mode diode lasers for the near and mid-infrared spectral region.…”
Section: Introductionmentioning
confidence: 99%